Solutions for the concrete readymix supply shortage on projects in the New Capital (IKN) of Indonesia - Pandit Purnajuara; Mursyid Hasan Basri (Global Academy of Multidisciplinary Studies, 2025)
Purpose: This study aimed to develop a comprehensive conceptual framework representing all aspects of the Readymix Concrete Supply Chain, including Environment, Product, Method, Supply Chain, Time, and Finance. It seeks to identify the main probable causes of operational issues using the Kepner-Tregoe analysis to support effective decision-making. Methodology: The Kepner-Tregoe analysis was applied to evaluate the situation and identify the root causes. SWOT analysis was then used to analyze the internal and external factors affecting company performance and generate strategic alternatives. Subject Matter Experts (SMEs) conducted pairwise comparisons based on five solution criteria: Cost, Flexibility & Adaptability, Schedule, Product Quality, and Supply Chain Reliability. The Analytical Hierarchy Process (AHP) was used to prioritize three alternative solutions for PT. Results: Findings indicate that constructing a new batching plant ranks as the top alternative, with a priority score of 50.3%, aligning strongly with the five key criteria and demonstrating high feasibility for implementation. Conclusion: The decision to establish a new batching plant can improve supply chain performance, provided that risk mitigation, budget planning, and site mapping are completed before the execution. Limitations: The study is limited by its reliance on expert judgment and single-company analysis, which may restrict generalizability. Contribution: This research offers a practical decision-making framework that integrates the Kepner-Tregoe, SWOT, and AHP methods to optimize operational efficiency and strategic planning in the concrete supply chain sector.